Co-expression of endoglucanase and cellobiohydrolase from yak rumen in lactic acid bacteria and its preliminary application in whole-plant corn silage fermentation - Wan, Xuerui; SunKang, Yongjie; Chen, Yijun; Zhang, Zhao; Gou, Huitian; Xue, Yu; Wang, Chuan; Wei, Yaqin; Yang, Yuze (Frontiers in Microbiology, 2024)
Endoglucanase (EG) and cellobiohydrolase (CBH) which produced by microorganisms, have been widely used in industrial applications. In order to construct recombinant bacteria that produce high activity EG and CBH, in this study, eg (endoglucanase) and cbh (cellobiohydrolase) were cloned from the rumen microbial genome of yak and subsequently expressed independently and co-expressed within Lactococcus lactis NZ9000 (L.lactis NZ9000). The recombinant strains L.lactis NZ9000/pMG36e-usp45-cbh（L.lactis-cbh）, L.lactis NZ9000/pMG36e-usp45-eg（L.lactis-eg）, and L.lactis NZ9000/pMG36e-usp45-eg-usp45-cbh（L.lactis-eg-cbh）were successfully constructed and demonstrated the ability to secrete EG, CBH, and EG-CBH. The sodium carboxymethyl cellulose activity of the recombinant enzyme EG was the highest, and the regenerated amorphous cellulose (RAC) was the specific substrate of the recombinant enzyme CBH, and EG-CBH. The optimum reaction temperature of the recombinant enzyme CBH was 60 ℃, while the recombinant enzymes EG and EG-CBH were tolerant to higher temperatures (80 ℃). The optimum reaction pH of EG, CBH, and EG-CBH was 6.0. Mn2+, Fe2+, Cu2+, and Co2+ could promote the activity of CBH. Similarly, Fe2+, Ba2+, and higher concentrations of Ca2+, Cu2+, and Co2+ could promote the activity of EG-CBH. The addition of engineered strains to whole-plant corn silage improved the nutritional quality of the feed, with the lowest pH, acid detergent fiber (ADF), and neutral detergent fiber (NDF) contents observed in silage from the L.lactis-eg group (P<0.05), and the lowest ammonia nitrogen (NH3-N) , and highest lactic acid (LA) and crude protein (CP) contents in silage from the L.lactis-eg+L.lactis-cbh group (P<0.05), while the silage quality in the L.lactis-cbh group was not satisfactory. Consequently, the recombinant strains L.lactis-cbh, L.lactis-eg, and L.lactis-eg-cbh were successfully constructed, which could successfully expressed EG, CBH, and EG-CBH. L.lactis-eg promoted silage fermentation by degrading cellulose to produce sugar, enabling the secretory expression of EG, CBH, and EG-CBH for potential industrial applications in cellulose degradation.